Etika Komputer dalam Implementasi Sistem ERP Odoo pada UMKM Sasukun Cafe - Lazarus Lazarus; Melda Agnes Manuhutu; Natasya Virginia Leuwol; Serly Serly; Jefri Jefri; Reiner Reiner; Samuel Samuel; Delfin Delfin; Lulu Jola Uktolseja (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2025)
Sasukun Cafe is one of the micro, small, and medium enterprises (MSMEs) engaged in the culinary sector with an operational scale that continues to grow. As the business grows, this café is faced with a number of managerial challenges such as inefficient management of raw material stocks, recording sales transactions that are still done manually, and inaccuracies in the bookkeeping system. This condition has the potential to reduce operational efficiency and accuracy, as well as hinder data-driven decision-making processes. To overcome these problems, this program aims to implement an Odoo-based Enterprise Resource Planning (ERP) system as an integrative solution to unify all business processes in one centralized and automated information system. The method used in this program is a case study with a qualitative descriptive approach. The implementation process includes identifying business needs, installing and configuring key Odoo modules such as Inventory, Sales, Purchasing, and Accounting, migrating initial data from legacy systems to the Odoo platform, training operational staff, and evaluating post-implementation system performance. The results of the implementation show that the use of Odoo ERP is able to significantly increase operational efficiency by up to 35%, minimize errors in stock recording and financial transactions, and speed up the process of preparing financial and managerial reports. In addition, this ERP system also provides convenience for management in conducting accurate real-time data analysis. The conclusion of this program states that the implementation of Odoo-based ERP systems has proven to be effective, flexible, and affordable in increasing the competitiveness and operational professionalism of MSMEs, especially in the food and beverage sector. This implementation also provides a strong foundation for MSMEs to develop sustainably in the digital era.